2023
DOI: 10.1001/jamaophthalmol.2023.0578
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Pattern and Injury Mechanism of Intimate Partner Violence–Related Ocular Trauma in the US

Abstract: ImportanceIntimate partner violence (IPV) is an important cause of death and disability worldwide. The literature estimates that 45% of IPV injuries involve the eyes. Many medical fields have increased IPV-related research; however, ophthalmology IPV research remains rare.ObjectiveTo evaluate the epidemiologic pattern and injury mechanism of IPV related to ocular trauma.Design, Setting, and ParticipantsThis study was a retrospective cross-sectional analysis with deidentified data using the International Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Socioeconomic indicators of health are often associated with injury rates. Access to economic resources and income levels were key risk factors for IPV reported by Alik et al 3 The relative risk of IPV was higher in persons with Medicaid and for female individuals or those with Black racial background. However, the racial background of patients with injuries overall was approximately 50% White and 25% Black.…”
Section: Demographicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Socioeconomic indicators of health are often associated with injury rates. Access to economic resources and income levels were key risk factors for IPV reported by Alik et al 3 The relative risk of IPV was higher in persons with Medicaid and for female individuals or those with Black racial background. However, the racial background of patients with injuries overall was approximately 50% White and 25% Black.…”
Section: Demographicsmentioning
confidence: 99%
“…1 Alcohol is often associated with ocular trauma, with 30% of trauma cases at a regional hospital in Australia involving alcohol; this figure is rising to 76% in assault-related cases and 85.2% for Indigenous Australians. 6 Alik et al 3 found that female individuals were at greater odds of alcohol use, with 42.5% screening positive for alcohol use, but had negative drug screens.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations